MOLECULAR IDENTIFICATION OF ISOLATES ANAPLASMA MARGINALE FOUND IN BLOOD OF CATTLE ON THE TERRITORY OF MOSCOW REGION - F. I. Vasilevich; S. N. Kovalchuk; A. V. Babiy; A. V. Arkhipov; A. L. Arkhipova; T. T. Glazko; G. Yu. Kosovskiy (Российский паразитологический журнал, 2019)
Objective of research: To detect and identify by molecular and genetic methods isolates Anaplasma marginale circulating on the territory of Moscow region. Materials and methods: Blood samples were taken from cattle on the territory of Moscow region in 2015. DNA was isolated from whole blood by the kit «Sorb-M». Identification of animals infected with A. marginale and estimation of the parasitemia level were carried out by real-time PCR methods. Typing of A. marginale strains was performed by modifying the primer structure. The received gene fragments were cloned in Escherichia сoli cells. Targeted selection of recombinant clones of E. coli was conducted by PCR methods using standard primers M13 with the following analysis of reaction products by 1,5% agarose gel electrophoresis. Results and discussion: It was shown that seven of thirty animals were carriers of A. marginale strains; levels of parasitemia range from 3,6 × 103 to 5,4 × 105 per 1 ml blood. The analysis of msp4 gene sequence of A. marginale isolates shows their belonging to two already known genotypes. The results obtained can be used for epidemiological monitoring of anaplasmosis on the territory of Moscow region as well as taken into account for development of vaccines.